Relationship between Perception of Individual Susceptibility and Barriers to Treatment Action in Scabies Patients - Elvira Revita; Dewi Putri Dayani; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2021)
Background: Scabies is found in crowded residential areas such as orphanages, dormitories, prisons, and Islamic boarding schools. In 2017, it was reported that scabies was among the 15 most common types of skin infections in Sumenep District, which reported 12,229 cases of scabies. Purpose: This study aims to analyze the relationship between the perception of individual susceptibility and barriers to treatment action in scabies patients at the Nasy’atul Muta’alimin Islamic Boarding School, Sumenep District, East Java. Methods: This research was an observational analytic study using a case-control design. The study population was patients with scabies in Nasy’atul Mutaalimin Islamic Boarding School, Sumenep District, East Java. The sample size was 70 people, consisting of 35 scabies patients who did not seek treatment as a case group and 35 scabies patients who did seek treatment as a control group. The sampling method used was simple random sampling. The two independent variables studied were the perception of individual susceptibility and barriers to treatment, while the dependent variable was treatment measures. The data analysis techniques employed were univariate and bivariate analysis. Results: This study shows that there are variables that have a relationship (p < 0.05) with the perception of individual susceptibility (OR = 99.00 95% CI 17.85 < OR < 548.86) and perceived barriers (OR = 29.00 95%, CI 7.968 < OR < 105.55). Conclusion: There is a relationship between the perception of individual susceptibility and barriers to treatment action in scabies patients.